MANAJEMEN PEMERINTAH DESA DALAM PENANGGULANGAN STUNTING DI DESA TANAH MERAH KECAMATAN TANAH MERAH KABUPATEN INDRAGIRI HILIR TAHUN 2022 - Nengsih, Isma Puspita; ', Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research seeks to answer the researcher's questions as follows, namely: How is the village government's management in overcoming stunting, what factors are the obstacles in overcoming stunting in Tanah Merah Village, Tanah Merah District, Indragiri Hilir Regency in 2022. This research also aims to describe government management village in overcoming stunting in Tanah Merah Village, then also to describe the factors that are obstacles in overcoming stunting in Tanah Merah Village, Tanah Merah District, Indragiri Hilir Regency. The type of research used by the author in this research is descriptive. Data collection techniques are interviews, literature study, and documentation. The data analysis technique in this research was carried out qualitatively. The results of this research explain that Village Government Management in Stunting Prevention in Tanah Merah Village has not been optimal due to the lack of village government management in stunting prevention issues, so that several indicators consist of policy and program planning, organization, government structure, financial management, guidance and development. personnel, general decision making, management programs, political supervision, have not gone well. In its implementation there are also several inhibiting factors such as Human Resources, Budget, and Infrastructure/Facilities and Infrastructure.